Case Report: Wernicke's encephalopathy after gastric surgery presenting as lactic acidosis and refractory thrombocytopenia - Qi Lin; Guanghua Li; Zhixiong Wang; Yu Zhang (Frontiers in Surgery, 2023)
Wernicke's encephalopathy (WE) is a severe neuropsychiatric disorder, mainly resulting from a nutritional deficiency of thiamine. WE is hard to detect at an early stage. Less than 20% of WE can be diagnosed during a patient’s lifetime, and WE tends to occur in patients with chronic alcoholism. Therefore, a large proportion of non-alcoholic WE patients are misdiagnosed. Lactate is an important by-product of anaerobic metabolism when the aerobic metabolism is blocked without thiamine, which can potentially serve as an alerting index for WE. Here, we report a case of a patient with WE who suffered gastric outlet obstruction following postoperative fasting, accompanied by lactic acidosis and refractory thrombocytopenia. A 67-year-old non-alcoholic woman who suffered hyperemesis for 2 months was diagnosed with gastric outlet obstruction (GOO). Gastric biopsies with endoscopy revealed gastric cancer, and total gastrectomy, together with D2 nodal dissection, was performed. She developed a coma with refractory thrombocytopenia rapidly after the surgical procedures were performed. The above conditions were treated not by the administration of antibiotics but by that of thiamine. We also found before the start of the procedures that she had a high level of blood lactate for a long period of time. Early diagnosis of WE is important because permanent injury can be caused to the central nervous system. Even today, the diagnosis of WE mainly depends on clinical symptoms, but occasionally, a typical triad occurs among WE patients. Therefore, a sensitive index for early diagnosis is critical for WE. Rising levels of blood lactate as a result of thiamine deficiency can serve as a warning for WE. In addition, we noted that this patient had a non-typical thiamine-sensitive refractory thrombocytopenia.